Recifes de Sabellaria wilsoni (Polychaeta: Sabellariidae) como habitat para a fauna macrobentônica de praias arenosas da ilha de Maiandeua/Algodoal (PA) - RODRIGUES, Bruno de Jesus Barros (2019)
The monitoring aspects of the population of some species of benthic invertebrates on Sabellaria wilsoni reefs of Maiandeua / Algodoal Island, aimed to evaluate the importance of habitat for them. Sampling monthly, from May 2008 to April 2009. Each month, 16 samples were collected reef using a cylindrical sampler (10 cm diameter and 20 cm in length). For volume using method water column displacement. Afterwards, the samples were fixed in 5% formalin saline, buffered with sodium tetraborate. In the laboratory the samples were passed in nylon mesh aperture of 0.3 mm, and the organisms retained, recorded, identified and stored in 70% ethyl alcohol. The organisms selected for analysis were: bivalves Prototacta pectorina and Cyrtopleura costata, the crustacean Alpheus armillatus, and the polychaete Allita succinea. Besides recorded in bivalves was estimated shell length, crustaceans was measured carapace length, made sexing and eggs in ovigerous females were classified into stages of maturation. Finally, to A. succinea were measured the length of prostomium and verified individuals epítoco (reproduction fase). Although present throughout the year, invertebrates differ in their temporal distribution and population structure. The average sizes of the bivalves were found well below the commonly recorded in literature, which might indicate that use reefs only during early stages of their life cycle. To A. armillatus were found juveniles and adults, with a predominance of females (70% of organisms), where 43% were ovigerous, with immature eggs and mature, indicating that the environment is a breeding and growth. Finally, for the polychaete reef is a habitat used throughout the life cycle of the species.